Molecular Mechanisms of Chondrocyte Proliferation and Differentiation - Chen, Hui; Tan, Xiao-Ning; Hu, Shi; Liu, Ren-Qin; Peng, Li-Hong; Li, Yong-Min; Wu, Ping (Frontiers in Cell and Developmental Biology, 2021)
Cartilage is a kind of connective tissue that buffers pressure and is essential to protect joint movement. It is difficult to self-recover once the cartilage damaged since the lack of blood vessels, lymph and nerve tissue. Repairing cartilage injury is mainly achieved by stimulating chondrocytes proliferation and extracellular matrix (ECM) synthesis. Cartilage homeostasis involves the regulation of multiple growth factors and the transduction of cellular signals. It is a very complicated process that has not been elucidated in detail. In this review, we summarized a variety of signaling molecules related to chondrocytes function. Especially, we described the correlation between chondrocyte-specific growth factors and cell signaling molecules. It has potential significance for guiding the treatment of cartilage injury.